An assessment of corporate governance reforms in the Philippines 2002-2009 - Wong, Debbie C. (Philippine Management Review, 2009)
This paper intends to present an update of the various corporate governance reforms in the Philippines since the adoption of the 2002 Code of Corporate Governance issued by the Philippine Securities and Exchange Commission (SEC). A comparison of these reforms against the Sarbanes-Oxley Act in the United States is also shown. The paper ends by discussing the various assessments conducted by various local and international organizations and how these corporate governance reforms in the Philippines compare with those in our Asian neighbors.